Otimização de fluxo em redes na gestão financeira do caixa: aplicação em uma empresa do setor agroindustrial - Pacheco, José Vinícius de Avila (2007)
Cash flow management is a financial problem that involves the efficient management of cash, short-term investments and short-term loans. In this study, we formulate the cash flow problem encountered in a typical agro-industrial company as a network optimization problem. Two examples using a linear programming model were studied: in the first example, the original model were used to support operational cash flow decisions, in the second example, the model were extended to a tactical planning of loan payments. The mathematic models are resolved in the solver tool that is an add-in of Microsoft Excel. Spreadsheets are of wide applicability for analytical work in business. The model has the potential of being flexible and to maximize the cash return from the final planning period in real-life situations